Mythical Images of the Solar Carriage and Ship: the Heavenly Body in the Course of an Astronomical Day - Laurinkienė, Nijolė (Tautosakos darbai, 2017)
The article focuses on the mythical image of the Sun, one of the most important heavenly bodies that people used to observe since times immemorial. The author uses various sources of the Baltic religion and mythology, Lithuanian and Latvian folklore and linguistic data. Her aim is revealing the meaning of the mythical image of the Sun as reflected by the traditional verbal heritage, and analyzing its origins. The investigation is confined, however, to the aspects of the solar image symbolizing the course of Sun’s movement during an astronomical day. Special attention is given to the solar carriage and ship, which are particularly deeply rooted in the Baltic past and in the ancient European spiritual culture.Veneration of the Sun was rather prominent in the eastern and western Baltic territories. Although data related to the Sun’s divine character are rather scant and obscure in the sources of the Baltic religion and mythology, the outstanding role of this heavenly body in the Baltic mythical worldview is unmistakable. The common definition of the Sun is mother (Lithuanian motinėlė, Latvian māmuliņa) in the Lithuanian and Latvian folklore, particularly the folksongs that frequently mention the heavenly bodies. Such characterization also reflects status of the Sun in the ancient hierarchy of the mythical values, testifying to the vernacular concept of this luminary, characterized by employing a familiar notion from the social sphere. This leads the author to conclude that the Sun was regarded as the most important luminary in the Baltic mythical worldview, as well as a significant dominant of cosmos that enveloped humans and was perceived by them. This universal image is characterized by global dissemination; fragments of its shape and manifestations in mythology, folklore, rituals and beliefs are preserved by the Balts as well.Various aspects of the Sun in the Baltic mythology can be discussed, including manifestations of this heavenly body in an astronomical cycle. Lithuanians and Latvians, just like the ancient Indians, Greeks and Germans, used to describe the Sun’s “travelling” and movement in relation to the Earth in the course of day and night by employing typical personifications of the Sun as riding in a carriage or sailing by a ship, as trundling out onto the sky in the morning and submersing into the watery depths in the evening. The rhythmic cycle of these travels encompasses our daily activities; it is the daily rhythm and cycle of our life endowed with mythical symbolism.
Keywords: -